Population Shuffling of Protein Conformations1. (6th November 2014) - Smith, Colin A.; Ban, David; Pratihar, Supriya; Giller, Karin; Schwiegk, Claudia; de Groot, Bert L.; Becker, Stefan; Griesinger, Christian; Lee, Donghan
Abstract Motions play a vital role in the functions of many proteins. Discrete conformational transitions to excited states, happening on timescales of hundreds of microseconds, have been extensively characterized. On the other hand, the dynamics of the ground state are widely unexplored. Newly developed high‐power relaxation dispersion experiments allow the detection of motions up to a one‐digit microsecond timescale. These experiments showed that side chains in the hydrophobic core as well as at protein–protein interaction surfaces of both ubiquitin and the third immunoglobulin binding domain of protein G move on the microsecond timescale. Both proteins exhibit plasticity to this microsecond motion through redistribution of the populations of their side‐chain rotamers, which interconvert on the picosecond to nanosecond timescale, making it likely that this "population shuffling" process is a general mechanism.